PEMBERDAYAAN KEWIRAUSAHAAN KOTP MELALUI PELATIHAN PEMBUATAN BEDDA LOTONG DENGAN TEKNIK HANDMADE - M, Riska.; Karina, Vivi Ervi; Devi, Sri; Aziza, ST. Nur; Purnamasari, Purnamasari; S, Samsidar; Trihandayani, Yolanda Eunike; Amalia, Reski; Musni, Nurul Fatanah; R, Syakriah Kamila Utami; Baso, B.Syukroni; Anas, Ayu Sheila Masita (Universitas Pahlawan Tuanku Tambusai, 2024)
Program